The Relationship Between Knowledge and Attitudes of Women of Reproductive Age Regarding Early Detection of Cervical Cancer with Iva Examination - Nadrah, Nailatun; Jolyarni D, Novica; Nasution, Fitriyani (International Journal Papier Advance and Scientific Review, 2023)
Cervical cancer is a major health issue for women all over the globe. Human papillomavirus (HPV) infection is the leading cause of cervical cancer, which is a cancer of the cervix. The more convenient, less costly, and doable Visual Inspection Method with Acetic Acid test (IVA) is in Indonesia. The researchers at Sigambal Health Center wanted to learn more about the WUS’s expertise and perspectives on IVA screening for cervical cancer in order to better serve their patients. This study used a cross-sectional, descriptive analytic strategy. Using data from 38 reproductive-age females. Study findings showed that among 38 responders, only 5 (31.2%) had a strong understanding of cervical cancer and 12 (63.2%) were supportive, whereas 22 (57.6%) WUS did not get IVA screening. There is a correlation between WUS knowledge of cervical cancer early detection and IVA, as measured by chi-square analysis, with a P-value of 0.045 0.05, rejecting H0 and accepting Ha. The link between WUS attitudes about acetate visual inspection (IVA) for the early diagnosis of cervical cancer and its prevalence was statistically significant (P = 0.009 0.05; Chi square analysis test on attitude). Health officers should encourage women to have Pap tests and use the IVA technique for WUS to screen for cervical cancer.